Plasminogen Activator Inhibitor-1 Levels in Patients with Chronic Angina Pectoris with or without Angiographic Evidence of Coronary Sclerosis - Huber, K; Resch, I; Stefenelli, Th; Lang, I; Probst, P; Kaindl, F; Binder, B R (Thrombosis and Haemostasis, 1990)
Increased plasma levels of plasminogen activator inhibitor-1 (PAI-1) have been shown to exist in 40 to 60% of patients with stable coronary artery disease and have been suggested to be responsible for the development of coronary thrombotic complications. However, it is also discussed whether PAI-1 elevation might mainly be due to variables like increased age or to reactive mechanisms caused e.g. by the chest pain itself. To exclude age dependent ui pain related influences, age-matched patients with stable angina pectoris (NHYA II) and angiographically proven coronary artery disease (CAD, n = 16) or without evidence for coronary sclerosis (variant angina, n = 10; angina-like syndrome with normal coronary angiogram, n = 5; non-CAD, n = 15) have been investigated for their plasma PAI-1 activity and t-PA antigen levels. The mean PAI activity in CAD patients (17.5 U/ml) was significantly higher than in non-CAD patients (9.6 U/ml) (p <0.0001). In the CAD patients no significant variation in plasma PAI-1 values could be demonstrated when related to the extent of the disease or to a history of previous myocardial infarction t-PA antigen was also elevated m CAD patients as compared to the non-CAD group (p <0.02). The results suggest therefore a strong correlation between coronary artery disease itself and elevated levels of components of the plasma fibrinolytic system.